The impact of United States colonization on the Rizalian tradition in cinema and literature a view of the popular arts as postcolonial historiography - Arriola, Joyce L. (2006)
The essay analyzes the ideological impact of United States (US) colonization on artistic productions on Jose Rizal, specifically in literature and film and how these works contribute to the discourse of the popular arts as postcolonial historiography. US cultural impact could be gleaned from how US cultural policies influenced Rizalian biographies and how these inspired literacy and cinematic productions on the hero. The Rizalian texts cited are films and novels produced from the time of US colonization to the Centennial celebration in 1988, published biographies and postmodern fictional takes on Rizalian biography. It discusses semiotic/linguistic constructions of Rizal attributed to US influences, artistic/literary forms, models and movements. It also analyzes the issues of spectatorship influenced by the Filipino reception of US culture. Rizalian filmmaking and literary productions are theoretically linked to the Hollywood narrative tradition and the models of literary education brought by the Thomasites. Contemporary historiography and Rizalian cinema are therefore offered as sites of analysis for more open and liberal forms of aesthetic inquiry and theoretical discourses on the subject. This is a revised version of the paper read at the Sangandaan 2003: An International Conference on Arts and Media in the Philippine-American Relations, 1899-2002 held on July 7-11, 2003 at the Philippine Social Science Council in Quezon City.
Includes bibliographical references (pages 70-74).